Digital modeling by biomedical informatics analysis predicts suppression of COVID-19 infectivity via ‘targeting oligonucleotide-directed devolution’ - Frank-Un Hong; Miguel Marciano Castro; Klaus D. Linse (Exploration of Digital Health Technologies)
Aim: Genetic instability represents the hallmark of carcinogenesis. For cancer, the retinoblastoma (RB) gene defect allowing genetic instability was successfully exploited to eliminate cancer. Similarly, this study aims to assess the genetic instability of the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) spike protein’s S1/S2 furin cleavage site in hopes of applying oligonucleotide-based therapeutics to suppress infectivity by exploiting hypermutability. Methods: The Basic Local Alignment Search Tool was used to search for homology. Protein or nucleotide sequences were obtained from the National Center for Biotechnology Information database. BioEdit was used for multiple sequence alignment. Python-enhanced molecular graphics program was used for molecular modeling. Results: To assess feasibility, comparative sequence alignment was performed on S1/S2 site plus juxtaposing residues of SARS-CoV-2 and avian infectious bronchitis virus (IBV) isolate AL/7052/97 that belongs to distinct genus. IBV amino acids correlating to 678-TNSPRRARSVASQS of SARS-CoV-2 spike protein were deciphered (nine identical, two conserved, two displaced, and one unconserved). The encoding nucleotides exhibited 14 identities, three transitions (C>U or U>C, two; G>A or A>G, one), and 15 transversions (U>A or A>U, eight; C>G or G>C, six; G>U or U>G, one) with mostly complementary base (14/15) for transversion. Analysis of SARS-CoV-2 variants corroborates that S1/S2 site continues to evolve. The overall data portrays an evolutionarily dynamic nature of S1/S2 site. The potential role of intragenomic ‘microhomology-mediated template switching’ by RNA-dependent RNA polymerase is described. Conclusions: To apply virolytic pressure, peptide-guided oligonucleotides targeting S1/S2 site-encoding sequences may be deployed to trigger genomic RNA degradation. A potential consequence is that resistant variants (if emerge) may carry mutation(s) in S1/S2 site-encoding sequence to abrogate hybridization, which (by default) may encode defective substrate for furin. Thus, through ‘targeting oligonucleotides directed devolution’ of S1/S2 site, the infectivity of SARS-CoV-2 may be attenuated. An alternative strategy of oligonucleotide-based therapeutic editing by adenosine deaminases acting on RNA (ADAR) is mentioned.